Culture and economic growth in selected European countries - Furicová, Veronika (2014)
The diploma thesis main goal is to show how cultural values are associated with economic growth. The thesis approaches the goal on theoretical and practical grounds. The theoretical part describes three economic growth models and perspectives to culture. The practical part relates to statistical analyses.